Neurological Involvement in Inherited Metabolic Diseases: An Overview - Ceravolo, Ferdinando; Sestito, Simona; Falvo, Francesca; Salpietro, Vincenzo; Polizzi, Agata; Ruggieri, Martino; Bruno, Mercuri Francesco; Concolino, Daniela (Journal of Pediatric Biochemistry, 2016)
Neurological involvement is a typical feature of several inherited metabolic diseases. The onset of signs and/or symptoms may appear as early as the first days of life or after an interval of normal or near-normal growth and development. Metabolic decomposition usually presents with a severe clinical phenotype, which include poor feeding, vomiting, lethargy, seizures, and loss of consciousness. This spectrum of manifestations is often fatal; however, severe neurological sequelae and/or regression of neurodevelopmental milestones can be the prominent signs in those who survive. Overall, treatable inborn errors of metabolism can be divided in three groups, namely: (Group 1) inborn errors of intermediary metabolism giving rise to acute or chronic intoxication; (Group 2) inborn errors of intermediary metabolism affect in genergetic processes; and (Group 3) inborn errors involving cellular organelles, including lysosomal, peroxisomal, glycosylation, and cholesterol synthesis defects. The spectrum of neurological manifestations includes developmental delay, seizures and epilepsy, pyramidal and extrapyramidal signs, movement disorders, vision and hearing impairment, peripheral neuropathy, and psychiatric abnormalities. The main anatomical/imaging patterns reflects selective vulnerability of nervous system substance and include atrophy, (predominantly) symmetrical abnormalities, and dysmyelination, As several patients with neurometabolic diseases responds favorably to therapeutic trials, early detection and early intervention is of utmost importance to prevent catabolic-related damage and to revert to normal or near-normal parameters neurodevelopmental milestones.
Keywords: inherited metabolic diseases; neurometabolic disorders; classification; neurological; imaging; therapy